PENGEMBALIAN BERKAS PERKARA OLEH PENUNTUT UMUM DALAM PRAPENUNTUTAN - Dwi Saputra, Anak Agung Gede Agung; Tangun Susila, I Wayan; Suartha, I Dewa Made (Kertha Wicara : Journal Ilmu Hukum, 2013)
Pre-prosecution process often occur, so that the file shufling through from theinvestigator to the public prosecutor, less completeness of case bundles will bringimpact in pre prosecution process. The aim of this study was to find out the file returnby prosecutor attorney in pre-presecution. This kind of study was the normative studywith case approach, statue, and analysis. This study result have been obtained asfollows, in the absence of a provision that gives the limitation of the number of times afile can be restored, this can be correlated to the intent of the law on the human rights,and for the sake of legal certainty for the seekers of justice, then return of the result oradditional outcome investigator by public prosecutor to the investigator, there must bea limitation criteria. As result that arised if the files of case do not returned from thepublic prosecutor if within 7 days the file do not return then file of investigationassumed resolved. The conclusion of this study are there is no rule the file of casereturn by prosecutor attorney in pre-presecution.
Keywords: Return, File of case, Public Prosecutor, Pre-prosecution